Surface waters as a sink and source of atmospheric gas phase ethanol. (February 2016) - Avery, G. Brooks; Foley, Laura; Carroll, Angela L.; Roebuck, Jesse Alan; Guy, Amanda; Mead, Ralph N.; Kieber, Robert J.; Willey, Joan D.; Skrabal, Stephen A.; Felix, J. David; Mullaugh, Katherine M.; Helms, John R.
Abstract: This study reports the first ethanol concentrations in fresh and estuarine waters and greatly expands the current data set for coastal ocean waters. Concentrations for 153 individual measurements of 11 freshwater sites ranged from 5 to 598 nM. Concentrations obtained for one estuarine transect ranged from 56 to 77 nM and levels in five coastal ocean depth profiles ranged from 81 to 334 nM. Variability in ethanol concentrations was high and appears to be driven primarily by photochemical and biological processes. 47 gas phase concentrations of ethanol were also obtained during this study to determine the surface water degree of saturation with respect to the atmosphere. Generally fresh and estuarine waters were undersaturated indicating they are not a source and may be a net sink for atmospheric ethanol in this region. Aqueous phase ethanol is likely converted rapidly to acetaldehyde in these aquatic ecosystems creating the undersaturated conditions resulting in this previously unrecognized sink for atmospheric ethanol. Coastal ocean waters may act as either a sink or source of atmospheric ethanol depending on the partial pressure of ethanol in the overlying air mass. Results from this study are significant because they suggest that surface waters may act as an important vector for the uptake of ethanol emitted into the atmosphere including ethanol from biofuel production and usage. Highlights: Fresh surface waters and estuarine waters are generally a net sink for atmospheric ethanol. Coastal waters can be either a sink or source of atmospheric ethanol. Ethanol (up to 598 nM) was found in each freshwater, estuarine and coastal sample collected.